Risk-based screening combined with a PCR-based test for group B streptococci diminishes the use of antibiotics in laboring women. (August 2017) - Khalil, Mohammed R.; Uldbjerg, Niels; Thorsen, Poul B.; Henriksen, Birgitte; Møller, Jens K.
Abstract: Objective: To assess the performance of a polymerase chain reaction – group B streptococci test (PCR-GBS test) – in deciding antibiotic prophylaxis in term laboring women. Study design: In this observational study, we enrolled 902 unselected Danish term pregnant women. During labor, midwives obtained vaginal swabs that were used for both GBS cultures (reference standard) and for the PCR-GBS test. Furthermore, we recorded the presence of risk factors for EOGBS (Early Onset Group B Streptococcal disease): (1) Bacteriuria during current pregnancy, (2) Prior infant with EOGBS (3) Temperature above 38.0 °C during labor, and (4) Rupture of membranes ≥18 h. Results: The prevalence of GBS carriers was 12% (104 of 902), the sensitivity of the PCR-GBS test 83% (86 of 104), and the specificity 97% (774 of 798). Among the 108 with one or more EOGBS-risk factors, GBS was present in 23% (25 of 108), the sensitivity 92% (23 of 25), and the specificity 89% (74 of 83). Conclusion: In programs that aim to treat all laboring women with vaginal GBS-colonization (12% in the present study) with penicillin, the PCR-GBS will perform well (sensitivity 83% and specificity 97%). In programs aiming to treat only GBS-carriers among those with risk factors of EOGBS, a reduction of penicillin usage by two-thirds from 12% to 4% may be possible.